2020
DOI: 10.1128/msystems.00187-20
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Symbiosis under Environmental Disturbances

Abstract: By virtue of complex ecologies, the behavior of mutualisms is challenging to study and nearly impossible to predict. However, laboratory engineered mutualistic systems facilitate a better understanding of their bare essentials. On the basis of an abstract theoretical model and a modifiable experimental yeast system, we explore the environmental limits of self-organized cooperation based on the production and use of specific metabolites. We develop and test the assumptions and stability of the theoretical model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…However, note that the model in [16] predicts that microbial communities in some cases are never in an ecologically stable state and are constantly in a state of flux with rapid turnover of antibiotics and strains, but this view does not seem to be widely held. Such communities can be perturbed via further ecological destabilisation of ongoing evolutionary dynamics [37, 38]. In particular, this could take the form of immigration of new individuals into a stable community or mutation of resident phenotypes, which can correspond to an increase in the number of strains N .…”
Section: Model and Resultsmentioning
confidence: 99%
“…However, note that the model in [16] predicts that microbial communities in some cases are never in an ecologically stable state and are constantly in a state of flux with rapid turnover of antibiotics and strains, but this view does not seem to be widely held. Such communities can be perturbed via further ecological destabilisation of ongoing evolutionary dynamics [37, 38]. In particular, this could take the form of immigration of new individuals into a stable community or mutation of resident phenotypes, which can correspond to an increase in the number of strains N .…”
Section: Model and Resultsmentioning
confidence: 99%
“…This theoretical framework is a part of a larger ongoing project on the evolution and ecology of synthetic communities ( 22 , 23 , 32 ). An application of an extended consortium system, and a key driver behind the development of this model, would be predicting the outcomes of ecosystem interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This has facilitated the development of synthetic yeast cross-feeding models of mutualism. A system of interdependent strains of yeast, one overproducing lysine and lacking adenine and the other overproducing adenine and lacking lysine, was developed in the study reported in reference 22 and analyzed in detail both biochemically and ecologically ( 17 , 32 ). The strains overproducing leucine and lacking tryptophan and vice versa were developed in the study reported in reference 23 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-efficacy, the belief in one's ability to perform tasks and face challenges, significantly influences students' engagement in learning and problem-solving in mathematics, leading to improved outcomes (Bandura, 2013;Cervone et al, 2020;Luu, 2023;Martin, 2020;Yentür, 2023). Concurrently, mathematical analysis skills, essential for critical thinking and problem-solving, enable students to dissect, understand, and apply mathematical concepts to complex problems, underscoring their relevance beyond academic settings into professional and daily decision-making (Denton & Gokhale, 2020;Satake et al, 2019;Uria-Albizuri et al, 2020). Therefore, integrating strategies to boost self-efficacy alongside developing analytical skills in mathematics curricula is paramount for preparing students to navigate and innovate within our rapidly changing world, emphasizing the intertwined roles of these competencies in lifelong learning and adaptability.…”
Section: Introductionmentioning
confidence: 99%